(untitled) (Research, Society and Development, 2021)
The wood frame construction system in Brazil has been increasing due to the spped and ease construction, resistance the environmental weather, the competitiveness in the civil construction and the sustainable issues. However, resistence to use this system of construction in Brazil is high. The objective of this work is to present the advantages and disadvantages of the characteristics of the construction system in woodframe addressing the sustainable responsibilities and the techniques used. For the execution of this work, systematic bibliographic research was performed as methodology. Few texts were found about the use of woodframe in Brazil that showed that this type of construction is scarce in the country due to problems such as lack of information to the public and for civil engineers in universities, lack of skilled workers and problems of awareness of the population that thinks this is a fragile and barely durable system. The improvement of teaching on drywall, therefore, also on woodframe, should be implemented in universities, the engineer should be the encourager and informer about new construction techniques, at least in Brazil.